2021
DOI: 10.1164/rccm.202101-0208le
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Thomson: Exposure to Active and Passive Tobacco Smoke on Urinary Eicosanoid Metabolites in Type 2 Asthma

Abstract: U-BIOPRED Study Group, on behalf of the U-BIOPRED Study Group. Urinary leukotriene E 4 and prostaglandin D 2 metabolites increase in adult and childhood severe asthma characterized by type 2 inflammation: a clinical observational study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…ILC2 numbers and PGD 2 concentrations in the bronchoalveolar lavage (BAL) fluid were reported to correlate after allergen challenge of mild asthmatics [25]. Moreover, metabolic products of PGD 2 were found in human serum [42], plasma, BAL [43] and urine [44,45] samples, however, their contribution to the asthmatic disease is poorly understood [20]. Studies on eosinophils in mice showed that ∆ 12 -PGJ 2 mobilizes eosinophils from the bone marrow and facilitates cell extravasation [18] which fits with the observation that PGD 2 is preferably converted to ∆ 12 -PGD 2 and ∆ 12 -PGJ 2 in blood plasma [12].…”
Section: Discussionmentioning
confidence: 99%
“…ILC2 numbers and PGD 2 concentrations in the bronchoalveolar lavage (BAL) fluid were reported to correlate after allergen challenge of mild asthmatics [25]. Moreover, metabolic products of PGD 2 were found in human serum [42], plasma, BAL [43] and urine [44,45] samples, however, their contribution to the asthmatic disease is poorly understood [20]. Studies on eosinophils in mice showed that ∆ 12 -PGJ 2 mobilizes eosinophils from the bone marrow and facilitates cell extravasation [18] which fits with the observation that PGD 2 is preferably converted to ∆ 12 -PGD 2 and ∆ 12 -PGJ 2 in blood plasma [12].…”
Section: Discussionmentioning
confidence: 99%
“…14 They have also shown to be altered in atopic dermatitis and asthma. [133][134][135] As an example, ceramide was elevated in mice lungs after allergen challenge, contributing to reactive oxygen species generation, apoptosis and neutrophilic infiltrate, which characterize the severe asthmatic phenotype. 136 Metabolomics studies can be carried out either in noninvasive samples such as urine, faeces, saliva, and breath, in minimally invasive samples such as blood (serum and plasma) or in tissue biopsies (Figure 5).…”
Section: Metabolomicsmentioning
confidence: 99%
“…Among the metabolites, the studying of the lipids—lipidomics—has become an important field, as lipids have important roles in immune response regulation, and participate in cell signaling, growth, differentiation, and apoptosis 14 . They have also shown to be altered in atopic dermatitis and asthma 133–135 . As an example, ceramide was elevated in mice lungs after allergen challenge, contributing to reactive oxygen species generation, apoptosis and neutrophilic infiltrate, which characterize the severe asthmatic phenotype 136 …”
Section: Basic Omics Strategiesmentioning
confidence: 99%
“…In addition to linear regression, more advanced computational tools, such as ROIMCR ( 70), can also be used to reduce the batch effects and to identify metabolites that associate with immune responses. In terms of sampling tissues, in addition to blood cells and inflamed tissues, proteome and metabolome can also be measured in urine, which is thought to be a rich source but underestimated in recent studies (71)(72)(73). In addition, fecal metabolites are usually studied together with microbiota, which affects immune homeostasis and susceptibility of the host to immune-mediated diseases.…”
Section: Proteome and Metabolome Measurementmentioning
confidence: 99%